The circular economy concept applied to non-productive structures: Case of the wastewater processing Station of a Tannery Algeria - Necer Mohamed; Smain Rachid (African Journal of Environmental Economics and Management, 2015)
Leather industry on the one side boosts the local economic development, on the other side; it leads to the tremendous environment pollution and biological chains destruction. The goal of this paper is to underscore the necessity of implementing a model of circular economy (EC) in order to achieve sustainable development for developing country industries. While reviewing the reasons for the need to adopt the strategy of circular economy thus, to adopt cleaner production for the industries of developing countries, the special features of Algerian society which makes the use of circular economy necessary were also reviewed. It is important to develop a method for developing a priority for industrialists to work with in initiating best available practices, taking into accounts all of the company subsystems. It is important to broaden the application of the concept under the EC to business systems that have long been considered unproductive (wastewater treatment plants), in this case not taken into account by the traditional scheme EC as well as waste from other polluting industries. Companies have great opportunities to minimize economic losses and preserve the natural environment by getting rid of its waste resulted from tanning and also from external companies to operate the works known by their management difficult.